Youth: Including Africa’s young people in food systems - Mueller, Valerie; Rosenbach, Gracie; Thurlow, James (International Food Policy Research Institute, 2020)
African governments have made youth employment a policy priority, and African youth are demanding policies that improve their job prospects. KEY FINDINGS - Africa’s working-age population is growing by 20 million a year, and by 2050 will be growing by 30 million a year, raising questions about whether the region can create enough jobs for young people. - Concerns should not be overblown—the share of young people in the working-age population peaked in Africa at roughly 38 percent in 2001, not much larger than the peak share in other developing regions during their own “youth bulges.” Africa’s rural areas and food systems will have to play a bigger role in absorbing young job seekers than they did in other regions, given the continued growth of rural populations. - Opportunities in food systems for youth may be overestimated: Young farmers who are familiar with information technologies are not necessarily more likely than their elders to adopt improved inputs or increase productivity. Nor are they more likely to operate or work for a nonfarm enterprise or to migrate to large urban centers. - Broad-based development policies that create opportunities for all rural people may do more to support the growing youth population than polices designed specifically for youth.